The importance of the motor system in the development of music‐based forms of auditory rehabilitation. Issue 1 (1st June 2022) - Zendel, Benjamin Rich
Abstract: Hearing abilities decline with age, and one of the most commonly reported hearing issues in older adults is a difficulty understanding speech when there is loud background noise. Understanding speech in noise relies on numerous cognitive processes, including working memory, and is supported by numerous brain regions, including the motor and motor planning systems. Indeed, many working memory processes are supported by motor and premotor cortical regions. Interestingly, lifelong musicians and nonmusicians given music training over the course of weeks or months show an improved ability to understand speech when there is loud background noise. These benefits are associated with enhanced working memory abilities, and enhanced activity in motor and premotor cortical regions. Accordingly, it is likely that music training improves the coupling between the auditory and motor systems and promotes plasticity in these regions and regions that feed into auditory/motor areas. This leads to an enhanced ability to dynamically process incoming acoustic information, and is likely the reason that musicians and those who receive laboratory‐based music training are better able to understand speech when there is background noise. Critically, these findings suggest that music‐based forms of auditory rehabilitation are possible and should focus on tasks that promote auditory–motor interactions.